Effectiveness of Ergonomics-Based Occupational Health and Safety Assistance on Work Behavior and Welfare of Small-Scale Tofu Industry Workers: A Quasi-Experimental Study - al-manan, oesman raliby; Ulinuha, Faisa Nisa (Universitas Muhammadiyah Magelang, 2026)
Small-scale tofu manufacturing involves multiple occupational hazards including physical accidents, heat exposure, non-ergonomic working postures, and inadequate personal protective equipment. This study aimed to evaluate the effectiveness of an ergonomics-based occupational health and safety (OHS) assistance program on knowledge, attitude, and actual work behavior among tofu workers in Yogyakarta. A quasi-experimental pre-post design was employed with 17 respondents over a two-month intervention period. Evaluation instruments covered three components: a knowledge test (correct/incorrect), a 5-point Likert attitude scale, and a behavioral observation sheet (1–4 scale) across five OHS indicators. Results showed knowledge improvement from 76.5% to 94.1% (Δ +17.6%). Attitude scores improved significantly (M pre = 18.00 vs. M post = 18.65; t(16) = −2.28, p = .037, Cohen's d = 0.53). The most substantial change occurred in observed work behavior, with total mean scores rising from 8.12 to 16.35 (Δ +101.4%; t(16) = −16.11, p < .001, Cohen's d = 5.66). The largest single-indicator gain was in daily OHS communication (Δ +2.18 points). These findings indicate that participatory, environment-modification-based assistance is effective in changing OHS behavior among micro and small-scale enterprises